Open Papers - Abstracts of Oral Presentations - Editor, The (Nepal Journal of Epidemiology, 2014)
Abstracts of the Oral Presentations at the Open Papers session at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10187